Herbal medicines : development and validation of plant-derived medicines for human health - Bagetta, Giacinto (Clinical pharmacognosy series, 2012)
While discussion concerning the validity of the plant approach to nutrition and disease treatment continues, the explosion of natural product use has generated concern regarding their effectiveness and possible danger. Using a rational, sequential approach, this book explores the development of efficacious medicinal herbal products